Crossing the Long Occlusion: Combined Antegrade-Retrograde Rendezvous via Mid-SFA Puncture with an Overview of Hybrid Recanalization Techniques - Arumulla, Mithilesh; Samireddypalle, Yugandhar; A., Prudhvinath Reddy; Prabhu, Sridhar V.; S., Amitha Vikrama K. (Journal of Clinical Interventional Radiology ISVIR, 2025)
Long-segment infrainguinal occlusions challenge endovascular interventions. When standard antegrade and retrograde techniques fail, hybrid approaches become vital. We report a case of critical limb ischemia secondary to long-segment superficial femoral artery (SFA) and P1 popliteal occlusion. After failed antegrade recanalization and unsafe retrograde access, a mid-SFA puncture enabled retrograde guidewire entry and successful reentry. Antegrade snaring and balloon angioplasty followed. Mastery of hybrid methods—SAFARI (subintimal arterial flossing with antegrade-retrograde intervention), CART, reverse CART (controlled antegrade and retrograde tracking), PIERCE (percutaneous direct needle puncture of calcified plaque), and wire rendezvous—is crucial for success in complex peripheral interventions.
Keywords: wire rendezvous; retrograde access; hybrid techniques